Evidence that tetracycline analogs whose primary target is not the bacterial ribosome cause lysis of Escherichia coli. - Oliva, B (1992)
The modes of action of atypical tetracyclines that do not directly inhibit bacterial protein synthesis were investigated. The analogs tested, chelocardin, anhydrotetracycline, 6-thiatetracycline, anhydrochlortetracycline, and 4-epi-anhydrochlortetracycline, were bactericidal and caused the lysis of Escherichia coli accompanied by the release of the cytoplasmic enzyme beta-galactosidase into the supernatant. Examination by electron microscopy demonstrated that cells exposed to these analogs underwent marked morphological alterations that included the formation of numerous ghosts and the appearance of cellular debris in the culture medium. Although atypical tetracyclines promoted lysis in intact organisms, they did not cause lysis of E. coli spheroplasts, indicating that the analogs do not directly destroy the cytoplasmic membrane. These agents may promote cell lysis and death by interfering with the membrane's electrochemical gradient, which in turn leads to stimulation of autolytic enzyme activity and cellular lysis. The results support recently published data which indicate that tetracyclines are divisible into two classes on the basis of their modes of action.